2016
DOI: 10.1111/cdev.12540
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ Descriptions of a Situation Can Influence Children's Appraisal, Feelings, and Subsequent Psychological Functions

Abstract: This study examined how an adult's descriptions of a situation could influence children's appraisal, feelings, and subsequent psychological functions. After baseline measures, 81 middle-class Singaporean kindergarten children (Mage  = 5.6 years, SD = 0.6) were exposed to an ambiguous accident and provided with positive, negative, or no descriptions of the accident. Children's appraisal of the experience, feelings of pleasantness, motivation to play a new game, confidence in playing the new game well, and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…It seems plausible. For example, Qu and Lim (in press) have found that an adult can not only influence children’s cognitive and affective responses in one situation, but can also influence children’s approach to a subsequent new situation, even in the absence of the particular adult. Additionally, previous training studies have shown providing several sessions of explanations, feedback, and reminders can not only improve children’s cognitive flexibility but also children’s understanding of mental states (e.g., Espinet et al, 2013 ).…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
“…It seems plausible. For example, Qu and Lim (in press) have found that an adult can not only influence children’s cognitive and affective responses in one situation, but can also influence children’s approach to a subsequent new situation, even in the absence of the particular adult. Additionally, previous training studies have shown providing several sessions of explanations, feedback, and reminders can not only improve children’s cognitive flexibility but also children’s understanding of mental states (e.g., Espinet et al, 2013 ).…”
Section: Implications Limitations and Future Directionsmentioning
confidence: 99%
“…For example, experiments have shown that participants who are sure they have lost a game have more negative expectations and post hoc reconstructions than those who believe they still have a fair chance ( Wilson et al, 2004 ). Whether people feel self-threat might influence people’ reaction and expectation after bad feedback ( Qu and Lim, 2016 ). Some researchers have found that predicting participants’ well-being from a observer perspective and improving a poor test result to an excellent one resulted in higher levels of predicted well-being than those who consistently performed well ( Sjstad et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the theoretical view, a series of experiments conducted by Moore et al ( 2013a , b , 2014 ) showed that that instructing participants to focus on adequate personal resources to meet task demands successfully enhanced their challenge appraisal, whereas emphasizing high task demands and/or high required effort increased their threat appraisal. Moreover, information about the potential consequences conveyed by the experimenter can also alter participants' appraisals (Qu and Lim, 2016 ). In particular, highlighting the rewards for top performers prior to a motivated performance task engaged participants in a challenge state, whilst emphasizing the punishment for poor performers led them to a threat state (e.g., Moore et al, 2012 , 2013b ).…”
Section: Introductionmentioning
confidence: 99%